Towards sustainable biocontrol: inhibition of soil borne fungi by microalgae from harsh environments - Eckstien, Dikla; Maximov, Noga; Margolis, Nofet; Raanan, Hagai (Frontiers in Microbiology, 2024)
Using microorganisms as biocontrol agents against soilborne plant pathogens is a promising alternative to chemical pesticides. However, only some biocontrol agents have proven effective under field conditions.Using microorganisms as biocontrol agents against soilborne plant pathogens is a promising alternative to chemical pesticides, but only some biocontrol agents have proven effective under field conditions. This study explores the potential of highly resilient microalgae isolated from harsh environments, such as Biological Soil Crusts and agricultural fields in semi-arid regions, as a novel and sustainable approach to biocontrol. Fifty-nine microalgal strains, including thirteen cyanobacteria and forty-six green algae, were isolated and identified. Dual-culture plate assays and toxicity tests of microalgal growth media were conducted to evaluate the antifungal activity of the isolates against eight representative soilborne pathogens. The results showed that many microalgae strains exhibited significant inhibitory effects on the growth of specific fungal pathogens, although the activity varied among different microalgal strains and pathogen species. Some strains even promoted the growth of certain fungi. The lack of a clear pattern in the antifungal activity highlights the complexity and specificity of the interactions between microalgae and soilborne pathogens. An "Inhibition Effectiveness" metric was developed to quantify biocontrol potential based on fungal growth inhibition. The green algal genus Desmodesmus, particularly Desmodesmus subspicatus isolates, showed higher antifungal efficacy than other genera. While the inhibitory mechanisms remain unclear, the results demonstrate the promising biocontrol capabilities of microalgae from extreme environments like BSCs. Further research could unlock novel opportunities for sustainable disease management by harnessing specific microalgal strains or synergistic strain combinations targeting soilborne pathogens.